Nonfarm participation and food consumption - GENEMO, Kedir Bekeru (KDI School, 2018)
The effect of rural nonfarm economic participation has become the focus of international concern given the challenge in low production in the agricultural sector and the bulk of the population lives in rural areas of developing countries. This paper seeks to observe the effect of nonfarm participation on food consumption in rural Ethiopia. Data for this study were obtained from the Ethiopian Socioeconomic Survey and World Bank living standard measurement survey for Integrated Surveys of Agriculture collected in 2014 and 2016. The data were collected repeatedly on each household comprising panel data set. We examined the effect of nonfarm economic participation using instrumental variable panel fixed effect model and generalized estimating equation. We find that participation in nonfarm activities has significantly improved food consumption, but it has shown no significant effect in improving food security in rural Ethiopia. This result may be connected with sustaining the development of rural areas.
Thesis(Master) --KDI School:Master of Public Policy,2018